2023
DOI: 10.14740/jocmr4845
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serum Sodium at Acute Kidney Injury Onset Predicts In-Hospital Death

Abstract: Background: Over the last decades, acute kidney injury (AKI) has been identified as a potentially fatal diagnosis which substantially increases in-hospital mortality in the short term and morbidity/mortality in the long term. However, reliable biomarkers for predicting AKI-associated outcomes are still missing. In this study, we assessed whether serum sodium, measured at different time points during the in-hospital treatment period, provided prognostic information in AKI.Methods: This was a retrospective, obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In a recent study conducted by our group [ 39 ], de novo AKI was detected using an in-hospital AKI alert system. This system automatically notifies the responsible nephrologist if either criterion 1 or 2 of the Kidney Disease: Improving Global Outcomes (KDIGO) clinical practice guidelines for AKI [ 40 ] is met.…”
Section: Hypernatremia In Emerging and Established Akimentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study conducted by our group [ 39 ], de novo AKI was detected using an in-hospital AKI alert system. This system automatically notifies the responsible nephrologist if either criterion 1 or 2 of the Kidney Disease: Improving Global Outcomes (KDIGO) clinical practice guidelines for AKI [ 40 ] is met.…”
Section: Hypernatremia In Emerging and Established Akimentioning
confidence: 99%
“…Although the study was designed retrospectively, it demonstrated the significant prognostic value of serum sodium in predicting outcomes in emerging AKI. Table 2 [6,34,[36][37][38][39][40] provides a summary of studies investigating the risk prediction of hypernatremia in AKI.…”
Section: Hypernatremia In Emerging and Established Akimentioning
confidence: 99%
See 1 more Smart Citation